Predicting nature-based coastal protection by mangroves under extreme waves - Zhan Hu; Stijn Temmerman; Qin Zhu; Xinran Wang; Jinwei Wu; Tianping Xu; Ken Schoutens; Tomohiro Suzuki; Zhifeng Yang; Tjeerd J. Bouma (Proceedings of the National Academy of Sciences, 2025)
Forested wetlands such as mangroves are considered highly valuable for nature-based mitigation of coastal flooding. However, their wave attenuation capacity during extreme storms, when risks are highest, is rarely measured and remains challenging to predict. Here, we compile a unique dataset on the largest incident wave heights (0.39 to 1.44 m) ever recorded in forested wetlands, including our own measurements and literature data. Our analysis reveals that forested wetlands can significantly attenuate storm waves (35% over 3 wavelengths) except in rare near-submerged cases. Notably, 19 of the 20 existing formulations for vegetation drag coefficient, a key parameter for wave attenuation modeling, are inapplicable in storm conditions. Hence, we introduce an new approach to reliably predict wave attenuation during storms, without the need for drag coefficient determination nor modeling expertise. This approach offers coastal practitioners a new user-friendly tool to assess the effectiveness of nature-based solutions for storm hazard mitigation.